All Days 2012
DOI: 10.2118/162970-ms
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulics Optimization For Efficient Hole Cleaning in Deviated and Horizontal Wells

Abstract: Efficient cuttings transport and hole cleaning is a very important factor that must be considered during drilling operations. In inclined and horizontal drilling, hole cleaning is a common issue since there is high tendency for formation of cuttings bed in the hole which can lead to several complex problems. The optimization of cuttings transport depends on so many factors like hole angle, cutting size, drill string rotation, drill pipe eccentricity, bit hydraulics etc. This paper is designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…It is believed that, cuttings transported in the annulus are not always affected by a single parameter, but a combination of parameters to ensure efficient hole cleaning [4]. Other studies have also confirmed that increase in fluid velocity results in a decrease in cuttings accumulation in the wellbore [5][6][7]. Ozbayoglu and Sorgun [8] also conducted cuttings transport experiment and developed empirical correlations for estimating pressure losses with the presence of cuttings and drill pipe rotation in horizontal and inclined wellbores.…”
Section: Introductionmentioning
confidence: 97%
“…It is believed that, cuttings transported in the annulus are not always affected by a single parameter, but a combination of parameters to ensure efficient hole cleaning [4]. Other studies have also confirmed that increase in fluid velocity results in a decrease in cuttings accumulation in the wellbore [5][6][7]. Ozbayoglu and Sorgun [8] also conducted cuttings transport experiment and developed empirical correlations for estimating pressure losses with the presence of cuttings and drill pipe rotation in horizontal and inclined wellbores.…”
Section: Introductionmentioning
confidence: 97%
“…Ogunrinde y Dosunmu, (2012) developed a model that ensure an appropriate hole cleaning in the critical inclination interval (45° -60°) and was determined the optimal flow and ROP to reach a successful drilling [2].…”
Section: Theorical Frameworkmentioning
confidence: 99%
“…One of these problems is that offered by the mud in its contact with the wellbore and other well elements such as casing, DP, DC and other drilling jewelries [1]. ECD results from the circulation of DM in the wellbore [2][3] during pumping operations. ECD is a measure of the ABHP that is exerted on the formation during any drilling, completion or workover operations.…”
Section: Introductionmentioning
confidence: 99%